2000
DOI: 10.1006/dbio.2000.9846
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Ldb/NLI/Clim Orthologue ldb-1 Is Required for Neuronal Function

Abstract: LIM homeodomain (LIM-HD) and nuclear LIM-only proteins play important roles in a variety of developmental processes in animals. In some cases their activities are modulated by a nuclear LIM binding protein family called Ldb/NLI/Clim. Here we characterize the Ldb/NLI/Clim orthologue ldb-1 of the nematode Caenorhabditis elegans. Two alternatively spliced variants exist, which differ in their amino-termini. The ldb-1 orthologue of Caenorhabditis briggsae has the same structure as that of C. elegans and is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Using a conditional RNAi approach, we have examined lin-11 function during vulval morphogenesis and demonstrate that lin-11 is required in vulval progeny for wild-type patterning. Finally, we show that the LIM-binding protein LDB-1 (Cassata et al, 2000) plays a role in vulval differentiation by directly interacting with LIN-11.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Using a conditional RNAi approach, we have examined lin-11 function during vulval morphogenesis and demonstrate that lin-11 is required in vulval progeny for wild-type patterning. Finally, we show that the LIM-binding protein LDB-1 (Cassata et al, 2000) plays a role in vulval differentiation by directly interacting with LIN-11.…”
Section: Introductionmentioning
confidence: 75%
“…ldb-1::GFP expression is first detected in embryos towards the end of gastrulation (prior to the comma stage) and is seen in the vulval cells among other expression (Cassata et al, 2000) (not shown). In vulval cells ldb-1::GFP expression is observed in both the 1°as well as 2°lineage cells (Fig.…”
Section: The Lim Binding Protein Ldb-1 Plays a Role In Vulval Patterningmentioning
confidence: 95%
See 1 more Smart Citation
“…Although we cannot categorically rule out the alternative scenario that an ancient Ssdp protein gained a new functional proline-rich domain before invertebrate and vertebrate separation and that Ldb1 lost the consequently redundant element, the functional data confirm our model of the evolutionary change in the nematode lineage. It has been shown that Ldb1 is actively expressed during C. elegans development, that it is required for some neuronal function, and that knockdown of its expression by RNA interference leads to uncoordinated locomotion (8). However, Ssdp is expressed at a low level, and its RNA interference shows no obvious phenotype (29).…”
Section: Resultsmentioning
confidence: 99%
“…The fundamental and universal nature of this interaction is clear from evolutionary comparisons. The Ldb1 ortholog in Caenorhabditis elegans is also able to bind LIM domains (8), and Chip, the Drosophila homolog of Ldb1, can interact with fly and mammalian LIM proteins (9).…”
mentioning
confidence: 99%